Identification of Salmonella sp in Islamic Boarding School in Bath Water Sumbergempol Sudistrict - Hariyanto Hariyanto; Dora Dayu Rahma Turista; Nala Ulya; Emma Rizmanda (International Journal of Clinical Inventions and Medical Sciences, 2020)
Salmonella is a bacterium that causes typhoid fever. Salmonella sp is able to live in water, dry waste, dust and if these bacteria live in a suitable living place then the bacteria multiply reach infective dose. The bathroom water is usually used for various things one of them gargling it allows the pathogenic bacteria left in the mouth and swallowed into the digestive tract so causing abdominal pain and fever. The purpose of this study is to determine whether there are Salmonella sp bacteria in the bathwater bath in the boarding school. This research is descriptive research. Which was held on 7 to 10 May 2018 at the Microbiology Laboratory DIII Health Analyst STIKes Hutama Abdi Husada Tulungagung. Population in this research is all boarding school existing in Sumbergempol District, sampling technique in this research is total sampling, which obtained as many as 6 samples of boarding school. The instruments used are sterile tube, measuring pipette, incubator, plate, plate agar medium, aquadest, oven and laboratory equipment required. The results obtained that from 6 samples, 1 positive Salmonella sp bacteria and 5 samples of Salmonella sp bacteria. The results of the research are then analyzed descriptively. Based on the results of the study it can be concluded that 16.67% positive Salmonella sp identified and 83.33% negative or unidentified Salmonella sp. The presence of Salmonella sp in the bathroom tub is caused by a bathroom tub that has a distance with a septic tank less than 10 meters. Research on the identification of bacteria other than Salmonella sp is also needed to know the presence or absence of other bacteria that exist in the water bathtub boarding school District Sumbergempol.